2020
DOI: 10.5194/hess-24-473-2020
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on the power of parametric and nonparametric tests for trend detection in annual maximum series

Abstract: Abstract. The need to fit time series characterized by the presence of a trend or change points has generated increased interest in the investigation of nonstationary probability distributions in recent years. Considering that the available hydrological time series can be recognized as the observable part of a stochastic process with a definite probability distribution, two main topics can be tackled in this context: the first is related to the definition of an objective criterion for choosing whether the stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 52 publications
2
29
0
Order By: Relevance
“…According to this criterion, the model with the lowest value of AIC should be the better one among the set of models examined. Following the idea of exploiting model selection criteria for detecting changes in time series analysis, Totaro et al [14] proposed the use of AIC R , defined as the ratio between the AIC values obtained, respectively, from nonstationary and stationary candidate models. They showed that, through Monte Carlo numerical experiments, is possible to evaluate AIC R statistical distribution and find the AIC R,α threshold value corresponding to an assigned level of significance α .…”
Section: The Akaike Information Criteria Based Testmentioning
confidence: 99%
See 4 more Smart Citations
“…According to this criterion, the model with the lowest value of AIC should be the better one among the set of models examined. Following the idea of exploiting model selection criteria for detecting changes in time series analysis, Totaro et al [14] proposed the use of AIC R , defined as the ratio between the AIC values obtained, respectively, from nonstationary and stationary candidate models. They showed that, through Monte Carlo numerical experiments, is possible to evaluate AIC R statistical distribution and find the AIC R,α threshold value corresponding to an assigned level of significance α .…”
Section: The Akaike Information Criteria Based Testmentioning
confidence: 99%
“…The need for giving an appropriate evaluation of the power of the MK test was highlighted, among others, by Totaro et al [14]. They followed the approach proposed by Yue et al [15] that produced a numerical evaluation of the MK test power for Generalized Extreme Value (GEV) distributed samples.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations